ASSESSMENT OF THE IMPACT OF CIRCULAR ECONOMY COMPETITIVENESS AND INNOVATION ON EUROPEAN ECONOMIC GROWTH - Popović, Andrija; Ivanović-Djukić, Maja; Milijić, Ana (The European Journal of Applied Economics, 2022)
The world usage of raw materials is 70% higher than what can Earth safely renew. The Circular Economy represents a new model of economic development relying on the 7Rs (redesign, reduce, reuse, repair, renovate, recycle, and recover) to provide operational and strategic benefits on the micro, meso and macro level. This research aims to determine the impact that circular economy competitiveness and innovation have on economic growth within European countries by evaluating the impact of four independent variables selected from the European Commission Circular Economy monitoring framework on the GNI per capita. We have analysed the competitiveness through Values Added at Factor Cost (VAFC), Gross Investment in Tangible Goods (GITG) and Number of Employees (EMP) in Circular Economy, innovation through the Number of Patents in climate change mitigation technologies related to wastewater treatment or waste management (PAT), while the economic growth was estimated based on the GNI per capita annual growth rate (GNIpc). We applied correlation and regression methods to the sample of 25 European countries using the log-transformed data. The results show that the correlation between VAFC and GNIpc is moderate and significant but negative, while the correlation between GITG and EMP and GNIpc is not statistically significant.
Keywords: Circular Economy; Competitiveness; Economic Development; Sustainable Development; Europe